Breeding systems of floral colour forms in the Drosera cistiflora species complex. (26th August 2020) - von Witt, C. G.; Anderson, B.; Durbach, I. N.; Johnson, S. D.
Abstract: Variation in plant breeding systems has implications for pollinator‐mediated selection on floral traits and the ecology of populations. Here we evaluate pollinator contribution to seed production, self‐compatibility and pollen limitation in different floral colour forms of Drosera cistiflora sensu lato ( Droseraceae ). These insectivorous perennial plants are endemic to fynbos and renosterveld vegetation in the Cape Floristic Region of South Africa, and the species complex includes five floral colour forms (pink, purple, red, white and yellow), some of which are known to be pollinated by beetles. Controlled hand‐pollination experiments were conducted in 15 populations of D. cistiflora s.l. (two to four populations per floral colour form) to test whether the colour forms vary in their degree of self‐compatibility and their ability to produce seeds through autonomous self‐fertilization. Yellow‐flowered forms were highly self‐incompatible, while other floral colour forms exhibited partial self‐compatibility. Seed set resulting from autonomous selfing was very low, and pollinator dependence indices were high in all populations. Since hand cross‐pollination resulted in greater seed set than open pollination in 13 of the 15 populations, we inferred that seed production is generally pollen‐limited. Drosera cistiflora s.l. typically exhibits high levels of pollinator dependence and pollen limitation. This is unusual among Drosera species worldwide and suggests that pollinators are likely to mediate strong selection on attractive traits such as floral colour and size in D. cistiflora s.l . These results also suggest that the floral colour forms of D. cistiflora s.l. which are rare and threatened are likely to be vulnerable to local extinction if mutualisms were to collapse indefinitely. Abstract : Floral colour forms of the Drosera cistiflora species complex vary in their degree of self‐incompatibility and pollen limitation, but are generally pollinator‐dependent; rare forms are therefore vulnerable to mutualism collapse.